Restraint stress of male mice triggers apoptosis in spermatozoa and spermatogenic cells via activating the TNF-α system. Issue 2 (14th April 2020) - Zhang, Jie; Kong, De-Ling; Xiao, Bin; Yuan, Hong-Jie; Kong, Qiao-Qiao; Han, Xiao; Luo, Ming-Jiu; Tan, Jing-He
Summary: Studies have indicated that psychological stress impairs human fertility and that various stressors can induce apoptosis of testicular cells. However, the mechanisms by which psychological stress on males reduces semen quality and stressors induce apoptosis in testicular cells are largely unclear. Using a psychological (restraint) stress mouse model, we tested whether male psychological stress triggers apoptosis of spermatozoa and spermatogenic cells through activating tumour necrosis factor (TNF)-α signalling. Wild-type or TNF-α −/− male mice were restrained for 48 h before examination for apoptosis and expression of TNF-α and TNF receptor 1 (TNFR1) in spermatozoa, epididymis, seminiferous tubules and spermatogenic cells. The results showed that male restraint significantly decreased fertilization rate and mitochondrial membrane potential, while increasing levels of malondialdehyde, active caspase-3, TNF-α and TNFR1 in spermatozoa. Male restraint also increased apoptosis and expression of TNF-α and TNFR1 in caudae epididymides, seminiferous tubules and spermatogenic cells. Sperm quality was also significantly impaired when spermatozoa were recovered 35 days after male restraint. The restraint-induced damage to spermatozoa, epididymis and seminiferous tubules was significantly ameliorated in TNF-α −/− mice. Furthermore, incubation with soluble TNF-α significantly reduced sperm motility and fertilizing potential. Taken together, the results demonstrated that male psychological stress induces apoptosis in spermatozoa and spermatogenic cells through activating the TNF-α system and that the stress-induced apoptosis in spermatogenic cells can be translated into impaired quality in future spermatozoa.